2013
DOI: 10.1155/2013/903818
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mass Transfer, Radiation, Joule Heating, and Viscous Dissipation on Steady MHD Marangoni Convection Flow over a Flat Surface with Suction and Injection

Abstract: The combined effects of radiation and mass transfer on a steady MHD two-dimensional Marangoni convection flow over a flat surface in presence of Joule heating and viscous dissipation under influence of suction and injection is studied numerically. The general governing partial differential equations are transformed into a set of nonlinear ordinary differential equations by using unique similarity transformation. Numerical solutions of the similarity equations are obtained using the Runge-Kutta method along wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The dual solutions in thermosolutal Marangoni boundary layer flow towards a flat plate with suction/injection effect can be given in Hamid et al 3 The combined effects of radiation and mass transfer in MHD two-dimensional Marangoni convection flow over a flat surface with Joule heating, viscous dissipation and suction/injection are numerically studied by Ibrahim. 4 Sreenivasulu et al 5 reported the radiative impact in steady laminar thermosolutal Marangoni convection flow of an electrically conducting fluid over a flat surface with Joule heating and viscous dissipation. Lin et al 6 analyzed magnetohydrodynamic (MHD) thermocapillary Marangoni convection heat transfer in flow of an electrically conducting power-law fluid driven by temperature gradient.…”
Section: Introductionmentioning
confidence: 99%
“…The dual solutions in thermosolutal Marangoni boundary layer flow towards a flat plate with suction/injection effect can be given in Hamid et al 3 The combined effects of radiation and mass transfer in MHD two-dimensional Marangoni convection flow over a flat surface with Joule heating, viscous dissipation and suction/injection are numerically studied by Ibrahim. 4 Sreenivasulu et al 5 reported the radiative impact in steady laminar thermosolutal Marangoni convection flow of an electrically conducting fluid over a flat surface with Joule heating and viscous dissipation. Lin et al 6 analyzed magnetohydrodynamic (MHD) thermocapillary Marangoni convection heat transfer in flow of an electrically conducting power-law fluid driven by temperature gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Jai [19] investigated the study of viscous dissipation and chemical reaction effects on flow past a stretching porous surface in a porous medium. Also, detailed mathematical research on the mutual effects of mass transfer and radiation over a time-independent MHD two-dimensional Marangoni convection flow over a smooth surface in the presence of joule-heating and viscous dissipation under the influence of suction and injection is studied by Ibrahim [20].…”
Section: Introductionmentioning
confidence: 99%
“…Yih (1997) employed Keller-box algorithm to vet the mass transfer impact on the flows via surface. The numerical solution for the physical properties of the radiative fluid towards a flat surface in the presence of Joule heating was scrutinized by Ibrahim (2013). Reddy et al (2016) observed that heat transfer rate in spherically shaped nano particles is efficiently higher than that of cylindrical shaped nano particles when the flow is across a permeable flat plate.…”
Section: Introductionmentioning
confidence: 99%